El "vuelo" del dragón: La cultura del opio en la Lima del novecientos - Muñoz Cabrejo, Fanni (1998)
Lima at the end of the 19th century and the beginning of the 20th century can be analyzed as a period of change and a key stage for understanding how the experience of modernity developed in Lima society. For the State and the modernizing elite that led this process, it was not only a material modernization of the city, but also a series of reforms with the aim of creating a modern national culture and therefore a bourgeois individual. In this modernizing project, the presence of European immigrants in particular was seen as a means to realize this ideal.